Women's empowerment as a determinant of neonatal mortality in Sub-Saharan Africa: a narrative review focused on Nigeria - Joel-Medewase Victor Idowu; Wada Zechariah Ojima; Sayomi Bukola Adetutu; Adetoye Mayowa Mary; Ashaolu Joseph Oluwakayode; Olowolafe Tubosun Alex (Taylor & Francis Group, 2024)
Neonatal mortality remains a critical public health issue, with Sub-Saharan Africa (SSA) experiencing disproportionately high rates compared to other global regions. Notably, SSA and South Asia are the regions most lagging behind the Sustainable Development Goal (SDG) 3.2, aiming for <12 neonatal deaths per 1,000 live births by 2030. Within SSA, Nigeria, the most populous country, records the highest number of neonatal deaths annually. Given the structural similarities among SSA nations, this narrative review, focusing on Nigeria, explores effective strategies to reduce the neonatal mortality gap. Information about trends, risk factors, and prevalent lapses was obtained from literature from renowned databases like PubMed, Scopus, and Google Scholar, and grey literature consisting of reports from relevant governmental and non-governmental organizations. Critical risk factors commonly identified include inadequate antenatal care (less than three visits), lack of access to skilled and clean birth practices, limited healthcare accessibility, financial barriers, substandard environmental conditions, and nutritional shortfalls. This review highlights women's empowerment as an additional critical factor, often overlooked, in the efforts to decrease neonatal mortality rates. Improving women's empowerment indices, such as the Gender Inequality Index (GII), employment, and literacy, offers a promising avenue to curtail neonatal mortality rates in Nigeria and across SSA sustainably. While this is potentially a long-term solution, short and medium-term recommendations were also proffered. By integrating women's empowerment within a broader strategy to improve maternal and newborn health, Nigeria can advance towards securing a healthier future for its youngest population.